The Effect of Performance Management on The Quality of Services in The Population and Civil Registration Services Kota Medan - M Rizki; Ronald, Roy; Rambe, Saima (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study discusses the influence of performance management on the service quality of the Department of Population and Civil Registration of Deli Serdang Regency. This study consists of two variables, namely the Independent Variable (X) Performance Management and the Bound Variable (Y) Service Quality. The purpose of this study was to determine how big the influence of performance management on the service quality of the Department of Population and Civil Registration of Deli Serdang Regency. This research was conducted at the Department of Population and Civil Registration Deli Serdang Regency. The population of this study were the employees of the Department of Population and Civil Registration of Deli Serdang Regency, amounting to 48 people. So the research sample is 48 people, if the subject is less than 100, all can be taken so that the research is a population study. Furthermore, if the subject is more than 100 it can be taken 10-15% or more. So the sample of this study amounted to 48 people (all populations were sampled). The method used in this study is a quantitative method. Data collection techniques in this study are observation, interviews (interviews), questionnaires (questionnaires), literature studies and documentation studies. The data analysis technique used product moment correlation and hypothesis significance test. To determine the significant level of the influence of performance management on the service quality of the Deli Serdang Regency Population and Civil Registration Service, a hypothesis test was carried out on r by determining the 5% significance level. Determine the test r table n=48. It is known based on data processing that the result of the r value of the product moment table with n = 48 and the 95% confidence level or 5% error is 0.284 and the r count is 0.40. Thus that r count 0.40 > r table 0.284. This means that there is a big influence between Performance Management and Service Quality. Thus the proposed hypothesis can be accepted, namely the magnitude of the influence of performance management on the service quality of the Deli Serdang Regency Population and Civil Registration Service.